The phantom midge and a comparison of metapopulation structures - Berendonk, T; Bonsall, M (2002)
Two sister species of Chaoborus exist in Europe. They are found in two distinct habitats that differ strongly in habitat persistence time. Chaoborus flavicans is found primarily in lakes inhabited by fish, whereas Chaoborus crystallinus is found exclusively in small ponds without fish. Chaoborus flavicans has evolved an adaptive response to predatory fish. In the presence of fish chemicals it can migrate vertically in the water column and can thus avoid predation. Chaoborus flavicans can therefore coexist with fish. Chaoborus crystallinus avoids oviposition into water bodies that are inhabited by fish and hence lives only in small fish-free ponds. These differences lead to several testable hypotheses: (1) The extinction risk of local populations of C. crystallinus is higher than that for C. flavicans. (2) C. crystallinus has a higher dispersal probability than C. flavicans. (3) The spatial population structure of each species differ. The results from a 3-yr population survey verified the first hypothesis that the extinction risk for C. crystallinus is higher than for C. flavicans. Field and laboratory experiments confirmed the second hypothesis. The results showed that, although C. flavicans disperses faster, the probability that C. crystallinus individuals disperse farther than 1 km is almost an order of magnitude higher compared to C. flavicans. The comparison of the spatial population structure of the two species shows that Chaoborus live in two different population structures that are subject to different metapopulation processes. Chaoborus crystallinus exists in a Levins-metapopulation, while C. flavicans exhibits a mainland-island population structure; these findings confirmed the third hypothesis. These results show that two species of the same genus live in two very different metapopulation structures and therefore present an ideal system to test comparative hypotheses within metapopulation ecology.